The Marbles of the Roman Villa of Chiragan at Martres-Tolosane (Gallia Narbonensis) - Attanasio, Donato; Bruno, Matthias; Prochaska, Walter (Archäologischer Anzeiger, 2017)
100 marble artefacts originating from the Roman villa of Chiragan and now part of the collections of the Musée Saint-Raymond at Toulouse were analysed and include the Herakles reliefs, the mythological tondos, a series of small-scale ideal sculptures and the collection of private and imperial portraits present in the villa. The local marble of St Béat quarried on the Pyrenees was used for the Herakles reliefs, the tondos, and the coeval portraits of the owner of Chiragan and his family, all sculptures stylistically identified as works of Aphrodisian sculptors dated to the end of the 3rd century A.D. by Jean-Charles Balty or to the mid second half of the 4th century A.D. by Marianne Bergmann. Import marbles, mostly Asiatic from Göktepe and Iscehisar (Docimium), were used for nine small-scale artefacts probably imported as finished products. Quite unexpected is the pervasive use of the marble of Göktepe for portraits of the Roman imperial period that were mostly imported from Rome as finished products. 59 sculptures from Chiragan and 11 portraits discovered at Béziers in the 19th century were analysed (Göktepe 37, Paros 17, Docimium 5, St Béat 5, Carrara 6). Between the end of the 1st and the beginning of the 2nd century A.D. the marble of Göktepe rapidly replaced Parian lychnites as the sculptural marble of choice for high quality portraits. In late antiquity, marble use and workmanship at Chiragan were deeply affected by the wish to emulate urban models, but also met with the difficulty of importing foreign marbles to a region not easily reachable from the Mediterranean.